Pathogenicity and virulence factors of Escherichia coli discovered using next generation sequencing technologies and proteomics - Mudau, Khuthadzo L.; Ntobeng, Lesoka R.; Kalu, Chimdi M.; Tekere, Memory (Frontiers in Bacteriology, 2025)
Escherichia coli is a gastrointestinal bacterium previously known for its commensal activities in the human digestive systems. Their occurrence in drinking water and natural water sources has been used as a faecal pollution footprint or marker to determine the extent of pollution. However, their ability to cause diseases as an opportunistic bacterium is a global concern. Hence, unveiling their diverse virulence factors and pathogenicity through diverse technologies becomes pertinent. The advent of next-generation sequencing technologies and proteomics have significantly propelled these studies forward. Utilizing next-generation sequencing and proteomics, scientists have unveiled a multitude of pathogenicity and virulence factors linked to E. coli. This review underscores the advancements made in uncovering E. coli’s pathogenicity, virulence factors, and specific attributes through next-generation sequencing and selected proteomics investigations. The review presents and describes discovered pathogenicity and virulence factors. It concludes that while significant progress has been made, there is still much work to be done that can utilize next-generation sequencing and proteomics in this area of research fully. The in-depth study of E. coli’s virulence factors and pathogenicity could provide preventive/curative insight into a pattern or technologies that could be adopted to minimize the outbreak of disease associated with the bacterium even at their opportunistic level.